Investigating the nature of the secondary binding site of the human β1-adrenoceptor using fluorescent ligands and confocal microscopy - Gherbi, Karolina (2013)
CGP 12177 is a high affinity β-blocker that antagonises agonist responses mediated through the catecholamine binding site of the human β1-adrenoceptor (β1AR). However, CGP 12177 also exerts agonist activity through a secondary, low affinity “CGP 12177” binding site/conformational state of the β1AR. In this thesis, we aimed to further our understanding of the nature of the secondary “CGP 12177” site by investigating ligand-receptor interactions at this site at the single cell level, using fluorescent derivatives of CGP 12177 (BODIPY-TMR-CGP, BY-CGP) and propranolol (BODIPY630/650-S-PEG8-propranolol, BY-PROP) in confocal microscopy studies. Initial studies demonstrated that both fluorescent β-adrenoceptor ligands displayed similar pharmacology at the human β1AR to their respective parent compounds, and that both ligands allowed visualisation of β1AR expressed in CHO cells. Using BY-CGP in a live cell fluorescence-based automated screening assay revealed two-phase antagonist displacement binding curves. In subsequent kinetic binding studies performed on a confocal perfusion system, we used infinite dilution conditions to determine dissociation rates of BY-CGP in the absence and presence of unlabelled ligands at the single cell level. BY-CGP dissociation rates were enhanced in the presence of unlabelled ligands, thus highlighting an allosteric mechanism of action of CGP 12177 at the human β1AR. Preliminary data using bimolecular fluorescence complementation suggested that these co-operative interactions between the two β1-adrenoceptor binding sites were mediated across a β1-adrenoceptor homodimer interface.